SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-3332
|View full text |Cite
|
Sign up to set email alerts
|

Interface Pressure Distributions Through Structural Modifications

Abstract: Due to the friction forces acting at the rotor and pads interface, the pressure distribution at the interface is asymmetric in a disc brake system of normal floatingtype caliper design. The asymmetry and the high unevenness of the interface pressure distribution cause uneven wear and shorten life of pads. It has been speculated that these undesirable features promote disc brake squeal. This paper investigates the contact (interface) pressure distributions at the rotor and piston-pad interface in response to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 12 publications
2
12
0
1
Order By: Relevance
“…It is found that contact pressure distribution is almost identical in all three cases and its value increases with an increase in the angular velocity of the disc. This was also confirmed by Abu Bakar, Ouyang, and Cao (2003). It is believed that this increase can create the wear of the pads as they can leave deposits on the disc, giving rise to what is called "the third body".…”
Section: Effect Of Friction Coefficientsupporting
confidence: 56%
“…It is found that contact pressure distribution is almost identical in all three cases and its value increases with an increase in the angular velocity of the disc. This was also confirmed by Abu Bakar, Ouyang, and Cao (2003). It is believed that this increase can create the wear of the pads as they can leave deposits on the disc, giving rise to what is called "the third body".…”
Section: Effect Of Friction Coefficientsupporting
confidence: 56%
“…In particular, the stabilization of the system vibrations at the limit cycle obtained by the experimental analysis [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] is predicted here by introducing contact nonlinearities in the numerical model.…”
Section: Discussionmentioning
confidence: 99%
“…This method is still linear and cannot account for nonlinearities due to the disc rotation, instant contact stiffness, local detachment and local stick phenomena, materials nonlinearity, etc. Recent studies try to account for effects like disc rotation and non-uniform contact pressure distribution [16][17][18]. Usually this approach is a good indicator for potential squeal frequencies, but it gives a poor idea on the propensity of the single squeal instability.…”
Section: Propensity To Instabilitymentioning
confidence: 99%
“…Finally they met there requirement with optimal modification. By their results the authors was stated that the right connection between piston ring and back plate in the axial direction will give better pressure distribution so that optimal contact will be established [6].In a braking phase the different contact behavior will occur between the components like pad and disc rotor. The author has carried out a study on thermo-mechanical dry contact behavior.…”
Section: Introductionmentioning
confidence: 99%